The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2012
DOI: 10.1371/journal.pone.0046975
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Alcohol Compounds on the Growth and Lipid Accumulation of Oleaginous Yeast Trichosporon fermentans

Abstract: The inhibitors present in dilute acid-treated lignocellulosic hydrolysates would show great effect on the growth and product formation of microorganisms. To understand their inhibitory law and mechanism on oleaginous microorganism could help improving the efficiency of lignocellulose hydrolysis, detoxification, and lipid fermentation. The effects of four representative alcohol compounds present in lignocellulosic hydrolysates, including furfuryl alcohol, vanillyl alcohol, catechol, hydroquinone on the cell gro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
16
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 31 publications
2
16
0
Order By: Relevance
“…The deleterious effect of inhibitory compounds including acetic acid, HMF, and furfural on oleaginous yeast growth and lipid accumulation has been well-documented by others (Huang et al, 2011;Hu et al, 2009;Chen et al, 2009) and confirmed by our study. While the effect of each inhibitor may vary across oleaginous yeast species and cultivation conditions, multiple studies have reported that furfural has a higher degree of inhibition compared to HMF (Huang et al, 2011;Chen et al, 2009;Zhao et al, 2012;Hu et al, 2009). This may account for the lower oil yields obtained using destarched hydrolysates which had a higher level of furfural compared to the whole bran hydrolysates (Fig.…”
Section: Fermentation Comparisonsupporting
confidence: 91%
“…The deleterious effect of inhibitory compounds including acetic acid, HMF, and furfural on oleaginous yeast growth and lipid accumulation has been well-documented by others (Huang et al, 2011;Hu et al, 2009;Chen et al, 2009) and confirmed by our study. While the effect of each inhibitor may vary across oleaginous yeast species and cultivation conditions, multiple studies have reported that furfural has a higher degree of inhibition compared to HMF (Huang et al, 2011;Chen et al, 2009;Zhao et al, 2012;Hu et al, 2009). This may account for the lower oil yields obtained using destarched hydrolysates which had a higher level of furfural compared to the whole bran hydrolysates (Fig.…”
Section: Fermentation Comparisonsupporting
confidence: 91%
“…1A and 1B). Furfural and 5-hydroxymethylfurfural are two furan derivatives, Chao Huang previously reported these two furans displayed lower toxicity to T. fermentans [7], however, some repoted Escherichia coli ATCC 1175, Z. mobilis ATCC 10988 and E. coli LY01 are more sensitive to furfural, the cell growth of those microorganism significantly decreased with the increase in concentration of furfural and 5-hydroxymethylfurfural [23][24][25], our results displayed C. glutamicum NC-1 showed some tolerance to furfural and 5-hydroxymethylfurfural at low concentration (above 1 g/L, Figs. 1A and 1B).…”
Section: Resultsmentioning
confidence: 99%
“…Malic enzyme is usually considered as the key one of the main enzymes in Krebs cycle, providing a supply of NADH to microorganisms [35]. Chao Huang reported the malic enzyme activity was inhibited while added aldehydes into medium for lipid synthesis in oleaginous microorganism [7]. In order to understand the effects of aldehydes on succinic acid accumulation under oxygen deprivation by C. glutamicum NC-1, so malic enzyme activity was detected while in accumulating succinic acid fermentation phase (Fig.…”
Section: Effect Of Aldehydes and Organic Acids On Malic Enzyme Activitymentioning
confidence: 99%
See 2 more Smart Citations